Tercapainya Tingkat Efektivitas Wakaf Uang Untuk Memberdayakan Kesejahteraan Mauquf ‘Alaih Di Yayasan Dana Sosial Al Falah (YDSF) Surabaya - Astrianisa Fathona; Moh. Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
As finance instrument, cash waqf becomes brand new in history of Islamic banking. Waqf is an act of worship by separating personal wealth to be public wealth in order to embody people prosperity. This research uses a qualitative approach with case study method. Data collection is conducted by interviewing informan (nazhir, wakif, and mauquf ‘alaih). The technique of analysis used in this study is reduce, present, and conclude the result. Then, the technique of data validity is source triangulation. The result of the study is the effectiveness of cash waqf’s program to distribute the fund to build a mosque. The level of effectiveness would be successful if all the element were totally accomplished and also affect people prosperity in maqashid syariah’s perspective.